PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PROGRAM PENGEMBANGAN DISTRIK KAJIAN DI PAPUA - Muchtar Muchtar (Sosio Konsepsia, 2010)
This study is aimed to describe the empowerment of communities through the Distric Development Program (PPD) in Papua. The approach of study is qualitative that emphasizes the essence and substance (the understanding, views, and responses) informans. The data obtained through the docuÂ·mentations and interviews. Informants determined purposively, namely apparatus Village Community Empowerment Board (BPMD) Papua Province as the manager of PPD. The study shows, although in the early implementation of the PPD program capable of executing the construction of basic rural infrastructure to take advantage of some program fu.nds plus local government organizations and channel some other program fu.nds to community groups for productive economic activities, but if observed, in particular the empowerment process has not occurred for the poor, because it has not happened yet transfer power to the poor. The program is utilized by certain circles (only), and the relative lack of social learning processes take place, because the savings and loan program is more nuanced. To that, suggestions are emphasized on the quality of courses at different levels of actors (especially the village level), namely: (a) they need to understand the program wellbriefing importance, (b) the need for implementation of programs to the community properly, which not only spread information, but also needs to be directed at raising awareness about the issues at hand, and the growth of the spirit to solve problems independently, (c) the need for assistance (local facilitators) in a sustainable manner against the perpetrators of the program at the village level, within a certain time, until they are assessed capable of handling the problem of poverty on their own citizens. Therefore, it is necessary escort officer who has the competence, visionis, and has good spirit.